Lumbar Disc Herniation with Contralateral Symptoms: A Case‐Series of 11 Patients and Literature Review - Qingyang Gao; Huiliang Yang; Umar Masood; Chunguang Zhou; Ying Cen; Yueming Song (Orthopaedic Surgery, 2023)
Objective Lumbar disc herniation (LDH) is a common pathology that typically causes unilateral radiculopathy on the same side as herniation, while patients may occasionally present with contralateral symptoms. Owing to the rare incidence of LDH with contralateral symptoms, the pathological mechanism remains unclear and the optimal surgical strategy is a subject of debate. This study aimed to provide new insights into the pathological mechanism of contralateral symptoms and assess the efficacy of ipsilateral hemilaminectomy and discectomy surgery in this population. Methods This study was a retrospective, single‐center, clinical case series, including 11 LDH cases with exclusive contralateral symptoms. We searched for LDH cases that were presented at our institution between January 2011 and December 2020. Adult LDH Patients with contralateral radicular pains were included, while those with ipsilateral radiculopathy, lumbar stenosis, foraminal stenosis on the symptomatic side, multilevel disc herniations, scoliosis, and lumbar operation history were excluded. Visual Analog Scale (VAS), clinical features, radiographic images, and other data were collected from the study cohort of 11 cases for further analysis. We also reviewed LDH cases in English literature from 1978 to 2023 to analyze their clinical characteristics and treatment. Results The incidence rate of LDH with contralateral symptoms in single‐level LDH cases was 0.32%. The average age of our 11 cases was 49.3 years old, and five of them were female (45.5%). All individuals had single‐level lateral LDH, with six cases (54.5%) located at L4‐5 and five cases (45.5%) located at L5‐S1. Upon admission, patients presented with lower back pain (seven cases, 63.6%), radicular pain (seven cases, 63.6%), hypoesthesia (seven cases, 63.6%), and muscle weakness (one case, 9.1%) on the contralateral side alone. Each case experienced ipsilateral hemilaminectomy and discectomy, and no lateral recess stenosis, hypertrophy of facets or ligaments, and sequestrated discs were found during surgery. All of them have good pain relief with two cases reporting no pain and nine cases reporting only mild pain at the last follow‐up. Conclusions Based on the surgical findings of our 11 LDH cases with contralateral symptoms, we hypothesized that the contralateral symptoms might be produced when the nerve root on the contralateral symptomatic side was tightly pulled by the herniated disc via the dural mater. Ipsilateral hemilaminectomy and discectomy surgery effectively and efficiently relieve the symptoms without postoperative complications for these patients.